METODE DAKWAH PADA ANAK USIA DINI MENURUT IMAM AL-GHAZALI DALAM KAJIAN KITAB IHYA ULUMUDDIN - Widia Jati Ningrum; Nirwan Syafrin; Hasan Basri Tanjung (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the appropriate method used in early childhood by looking at al Ghazali's view of early childhood in the book Ihya Ulumuddin. The research method used is qualitative with literature review and content analysis and descriptive methods. In literature review, researchers use written data, be it books, journals, or others, with a connection to the research being carried out. Da'wah method is one of the success factors of da'wah. Early childhood is a golden age in the journey of human life, so this phase must be used to introduce the concept of Islamic life through da'wah. Based on the results of the research that has been carried out, from al Ghazali's view of early childhood in the book Ihya Ulumuddin, the right da'wah method used for children at this phase is bil-hikmah, da'wah bil wisdom, da'wah al-mau'izah al-hasanah, da'wah bil hal, da'wah methods in the world of education, applied da'wah methods, da'wah bi al-takrir wa al-muroja'ah, da'wah bi tabsyir wa tandzi, da'wah methods with supervision, da'wah bil qishah, and da'wah bi lu'bah. Keywords: Da’wah Method, Early Childhood, Imam Al Ghazali